Serological Analysis by Enzyme-Linked Immunosorbent Assay Using Recombinant Antigen LipL32 for the Diagnosis of Swine Leptospirosis - Hartleben, Cláudia P. (2013)
Leptospirosis is an important global zoonotic disease caused by pathogenic Leptospira spp. species. Swine leptospirosis has a major economic impact because pigs are sources of animal protein and by-products. The signs of swine leptospirosis are abortion, stillbirth, birth of weak or ill piglets, appearing 14–60 days after infection. The reference method for diagnosis of leptospirosis is the microscopic agglutination test (MAT), in which serum samples are reacted with live antigen suspensions of leptospiral serovars. However, MAT is laborious and time consuming as a diagnostic procedure when dealing with a large number of samples; therefore, efforts are being made to develop novel, sensitive, and specific diagnostic tests for leptospirosis. In this study, a recombinant LipL32 based on enzyme-linked immunosorbent assay (rLipL32/ELISA) was evaluated as a screening test for the detection of pathogenic leptospiral-specific antibodies. A total of 86 swine serum samples tested by MAT were used to develop rLipL32/ELISA. Compared to positive and negative sera tested by MAT, rLipL32/ELISA showed 100 % sensitivity, 85.1 % specificity, and 91.86 % accuracy. No positive reaction for other bacterial diseases (enzootic pneumonia and brucellosis) was observed. The rLipL32/ELISA reported in this study is a specific, sensitive, and convenient test for the detection of antibodies against swine leptospiral infection and can be used as a rapid screening test in epidemiological surveys.